Fluorinated aggregated nanocarbon with high discharge voltage as cathode materials for alkali-metal primary batteries - Chen, Huixin; Yan, Ke; Zou, Yan; Xia, Qi; Kang, Xiaoyu; Yue, Hongjun; Chen, Ding (Frontiers in Chemistry, 2024)
Due to its exceptionally high theoretical energy density, fluorinated carbon has been recognized as a strong contender for the cathode material in lithium primary batteries particularly valued in aerospace and related industries. However, CFx cathode with high F/C ratio, which enables higher energy density, often suffer from inadequate rate capability and are unable to satisfy escalating demand. Furthermore, their intrinsic low discharge voltage imposes constraints on their applicability. In this study, a novel and high F/C ratio fluorinated carbon nanomaterials (FNC) enriched with semi-ionic C–F bonds is synthesized at a lower fluorination temperature, using aggregated nanocarbon as the precursor. The increased presence semi-ionic C–F bonds of the FNC enhances conductivity, thereby ameliorating ohmic polarization effects during initial discharge. In addition, the spherical shape and aggregated configuration of FNC facilitate the diffusion of Li+ to abundant active sites through continuous paths. Consequently, the FNC exhibits high discharge voltage of 3.15 V at 0.01C and superior rate capability in lithium primary batteries. At a high rate of 20C, power density of 33,694 W kg–1 and energy density of 1,250 Wh kg–1 are achieved. Moreover, FNC also demonstrates notable electrochemical performance in sodium/potassium-CFx primary batteries. This new-type alkali-metal/CFx primary batteries exhibit outstanding rate capability, rendering them with vast potential in high-power applications.